دراسة مواصفات وخواص بيض المائدة المعروض للاستهلاك البشري في الأسواق التجارية السورية - عبد العزيز فهيم; نيصافي علي (Latakia University Journal -Biological Sciences Series, 2019)
تم فحص 9000 بيضة معروضة للبيع في الأسواق المحلية. بلغت نسبة التشوهات في شكل القشرة 7%، ونسبة التلوث بمواد الفرشة والزرق على القشرة 30%، ونسبة الكسور %4، والشروخ %2، والبقع أو الشوائب 2%. وبلغت نسبة بيض الدرجة الممتازة % 8 ودرجة جيد جداً %32 ودرجة نخب أول 35% ونخب ثانٍ 25% ونخب ثالث 5% تبعا لمعايير نتائج الوزن. وبلغ العمر التقديري للبيض تبعاً لطريقة التعويم في المحلول الملحي 2-1 يوم لدى 55% و3 أيام لدى 30% و4 أيام لدى9 % وأكثر من 4 أيام لدى6 % منها. صنفت 23% من العينات بدرجة ممتازة و %62 نخب أول و13% نخب ثانٍ و2% نخب ثالث اعتمادا على نتائج قياس الحجرة الهوائية. راوحت قيم معامل الصفار في العينات المفحوصة بين 0,45 -0,50 لدى 62% منها وبين 0,40- 0,45 في 25% منها وما بين 0,30 -0,40 لدى 11% منها ودون 0,30 في %2 من تلك العينات. بلغت نسبة البيض الطازج درجة أولى 77% والبيض الطازج درجة ثانية 21% وغير الطازج 2% تبعاً لمعطيات حساب قيم وحدات هاوف. وبجمع نسب التغيرات الخارجية المؤثرة على الجودة والتغيرات الداخلية والوزن والعمر فإن 40 - 45% تقريباً من البيض يخالف المواصفات الأوروبية ولا يسمح بيعه للاستهلاك البشري. After the examination of 9000 eggs, the percentages of shell shape deformation, shell feces contamination, Gross cracks, shell hairline cracks ,mottled were 7%, 30%, 4%, 2%, 2% respectively. Depending on the weight results criteria’s, the proportions of excellent grad were 8%, very good grad 32%, the first class 35%, the second class 25% and the third class 5%. Due to the Saline water flotation method the egg’s age was estimated 1-2d. 55%, 3d. in 30%, 4d. in 9% and more than 4d. in 6% of in markets layout egg’s samples. 23% of samples were classified as excellent grad, 62% as 1.class, 13% as 2.class and 2% as 3.class according to the air space measurement. Yolk coefficient values rotated between (0,45-0,50) in 62%, between (0,40-0,45) in 25%, between (0,30-0,40) in 11% and less than 0,30% in 2% of tested samples. The proportion of fresh egg (first class) mounted 77%, fresh egg (second class) 21% and no fresh 2% depending on Hough Units. It was found about 43,5% of tested eggs were different from the European specifications, which made those eggs inconsumable.